2004
DOI: 10.1108/14777830410553915
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the environmental performance of printing and writing paper using life cycle assessment

Abstract: The potential environmental burdens over the whole life cycle of printing and writing paper produced in Portugal from Eucalyptus globulus were quantified, using Life Cycle Assessment (LCA) methodology. The main stages considered in the life cycle were: forest, pulp production, paper production, final disposal, energy production, chemical production and transports. The results suggest that pulp production processes have an important contribution to water emissions, resulting in a major contribution to eutrophic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…A study conducted on the performance evaluation of selected ceramic industry based on the ANOVA test found that the asset and sales management of the impoverished performers is to be improved as well as liquidity position has also to be improved [26] . A study made in Portugal on "environmental performance of printing and writing paper using Life Cycle Assessment" found that the life cycle of printing and writing papers includes various stages like a forest, pulp production, paper production, final disposal energy production, chemical production, and transports [27] .…”
Section: Review Of Literaturementioning
confidence: 99%
“…A study conducted on the performance evaluation of selected ceramic industry based on the ANOVA test found that the asset and sales management of the impoverished performers is to be improved as well as liquidity position has also to be improved [26] . A study made in Portugal on "environmental performance of printing and writing paper using Life Cycle Assessment" found that the life cycle of printing and writing papers includes various stages like a forest, pulp production, paper production, final disposal energy production, chemical production, and transports [27] .…”
Section: Review Of Literaturementioning
confidence: 99%
“…As a result, several LCA studies have been conducted around the world concerning this kind of industry (Rafenberg & Eric 1998;Larsen 2012). For instance in Portugal, Dias et al (2004) carried out a study on Eucalyptus globulus pulp-based printing paper in order to identify critical points in the process; they concluded that the paper production stage was a major contributor to eutrophication through water emissions, air emissions (especially for CO 2 and SO 2 ), non-renewable resource depletion, non-renewable energy consumption, and global warming. Similar conclusions were drawn by PricewaterhouseCoopers (PwC), who constructed a synthesis of different printed products' LCAs revealing the production stage as the most adverse to the environment; nevertheless, PwC stated that the level of contribution might vary based on the impacts considered and the special attributes of the process or product (PwC & FPAC 2010).…”
Section: Introductionmentioning
confidence: 99%